2021
DOI: 10.1111/hel.12848
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Helicobacter pylori infection, eradication therapy, and probiotics intervention on gastric microbiota in young adults

Abstract: Background:The impact of probiotics on non-Helicobacter pylori gastric microbiota and its role in microbial restoration after eradication were relatively unknown. We aimed to explore the effect of H. pylori eradication and probiotic intervention on gastric microbiota in young adults.Methods: Fifty-six H. pylori-negative and 95 H. pylori-positive subjects aged 19-30 were included in this study. H. pylori-infected individuals were randomly assigned to quadruple therapy, probiotics supplemented quadruple therapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 63 publications
3
46
0
Order By: Relevance
“…On this regard, the hypochloridria present in patients with chronic atrophic gastritis (CAG) might therefore represent an important cause of dysbiosis ( Engstrand and Lindberg, 2013 ). Gastric acid environment can also be affected by Helicobacter pylori ( H. pylori ) colonization that, in turn, may also influence the gastric microbial community structure and composition, leading to gastric dysbiosis ( Yuan et al., 2021 ) that may also play a role in the development of gastric adenocarcinoma ( Wen et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…On this regard, the hypochloridria present in patients with chronic atrophic gastritis (CAG) might therefore represent an important cause of dysbiosis ( Engstrand and Lindberg, 2013 ). Gastric acid environment can also be affected by Helicobacter pylori ( H. pylori ) colonization that, in turn, may also influence the gastric microbial community structure and composition, leading to gastric dysbiosis ( Yuan et al., 2021 ) that may also play a role in the development of gastric adenocarcinoma ( Wen et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In total, 2423 records were identified from the three databases (PubMed, Web of Science, and EMBASE) and one record was identified by review of references cited in included papers; 834 of them were repeatedly included from more than one search database and were excluded. Finally, nine articles ( Li et al., 2017 ; He et al., 2019 ; Serrano et al., 2019 ; Guo et al., 2020 ; Shin et al., 2020 ; Sung et al., 2020 ; Mao et al., 2021 ; Watanabe et al., 2021 ; Yuan et al., 2021 ) with 546 participants were included in the present study. The study selection process is shown in the PRISMA flow diagram ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included nine studies are shown in Table 1 . Six ( Li et al., 2017 ; He et al., 2019 ; Guo et al., 2020 ; Sung et al., 2020 ; Mao et al., 2021 ; Yuan et al., 2021 ) of them were conducted in China. For the participants, eight (8/9) studies focused on adults ( Li et al., 2017 ; He et al., 2019 ; Guo et al., 2020 ; Shin et al., 2020 ; Sung et al., 2020 ; Mao et al., 2021 ; Watanabe et al., 2021 ; Yuan et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations